Deforestation and capital accumulation: lessons from the Upper Kerinci region, Indonesia - Wibowo, D.H.; Tisdell, C.A.; Byron, R.N. (1997)
This study outlines a case where the behaviour of farmers in accumulating capital, rather than their poverty as commonly assumed, results in deforestation. Fieldwork was undertaken in the Upper Kerinci region of the island of Sumatera, Indonesia. A financial analysis of the "net income" streams received by farmers from deforestation is performed. Because forest lands can be "captured " and privatised through clearing and the subsequent agriculture have the capacity to produce high financial returns for farmers as well as to provide adequate capital to finance the next forest clearing. Such a capacity enables landless farmers to become land owners. Forest clearing also enables farmers to own a "long-term maturity bond" in the form of a cinnamon plantation. Poverty precludes poorer farmers from deforestation, and decisions to clear a forest rest mostly with more established farmers. Financial surpluses from outside the forestry and agricultural sectors are also used to finance forest clearing.